PEMBERDAYAAN PEREMPUAN UNTUK KESETARAAN & MENINGKATKAN PARTISIPASI DALAM PEMBANGUNAN LINGKUNGAN HIDUP - Suriani Nur (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2017)
Woman is one a human resource which is potential to be involved in development of environment. Amount of resident of Indonesia has plentyof woman gender to, despitefully woman represent environmental manager is suitable arrange natural resources and environment. Lack of knowledge of environment is one of the factor thatcause involvement of woman in development become minim. Conductingwomanparticipation is important to continue to improve woman clan self-capacities so that they can have self-confidence. Consequently woman clan can follow to participate and also act in all development in Indonesia which included in development of environment.